Arahan Reklamasi Lahan Pascatambang Tanah Liat (Clay) PT X Desa Temandang Kecamatan Merakurak Kabupaten Tuban Jawa Timur - Jatmiko, Novani Rahayu Ramadhanti; Lukito, Herwin; Suharwanto; Kristanto, Wisnu Aji Dwi; Yudono, Andi Renata Ade (Jurnal Lingkungan Kebumian Indonesia, 2023)
The clay mining activities carried out by PT X have resulted in an excavation pit, if there is no post-mining management that is carried out, it will decrease the productive land of the community along with native flora and fauna. This research aims to provide recommendations for post-mining reclamation direction of clay. The method used is survey and mapping method refers to Matric 17 of the Decree of The Minister of Energy and Mineral Resources of The Republic of Indonesia Number 1827 K/30/MEM/2018 about Reclamation Assessment Guidelines for Production Operation and the things to be analyzed are the stages of reclamation activities that have been carried out and purposive sampling method for soil sampling which will later be tested in the laboratory and then the results obtained will be matched with criteria for soil analysis results. Based on the results the land stewardship that carried out was leveling, stocking top soil, making drainage, and channel repairment. The revegetation carried out was planting of klampis, vetiver, and trembesi around the mine road. The final completion carried out is treatment up to two years of age, fertilization, and checking of reclaimed plants. The recommended clay post-mining land reclamation direction is revegetation with vetiver plants (cover crops) with spacing of (1x1) meter, eucalyptus (fast-growing plant) with spacing of (3x1) meter, and peanut (local plants) with spacing of (30x30) cm, then will be planted with a pot system.